Hypospadias Repair in Children: A 5-Year Experience from a Pediatric Surgery Department of Chittagong Medical College (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Hypospadias a very common condition in the children and the incidence is increasing.  Here we present our experience of managing hypospadias patients over the last five years.  Materials and methods: It was a retrospective study from 2014 to 2018 in the Department of Pediatric Surgery, Chattogram Medical College Hospital. Records of all hypospadias patients were analyzed and type of hypospadias, age at repair, type of repair and admission with complication of hypospadias were recorded.  Results:  A total of 492 boys were admitted with the diagnosis of hypospadias and 272 boys underwent hypospadias surgery. Distal penile hypospadias (148 patients, 30%) was the commonest variety followed by coronal hypospadias (144 patients, 29%). Age at surgery ranged from 6 months to 19 years with a mean age of 7±4 years. General anesthesia was given in 133 patients (64.7%) spinal anesthesia in 93 patients (31.8%) local anesthesia in 7 patients (2.4%) and caudal block in 3 patients (1%). Urethro-cutaneous fistula, failed urethroplasty and meatal stenosis are the admissions with hypospadias complications.  Conclusion: Hypospadias is still common with substantial number of complications. Health education is necessary to reduce age at surgery.JCMCTA 2020 ; 31 (1) : 38-41